Learning Dualism in Indonesian Education: Schools and Islamic Boarding Schools Within Parsons’ Theory of Social Action - Muhammad ilman Naafi'a; Achmad Siswanto; Abdi Rahmat; Fajar Wahyudi Utomo; Muhammad Idris (SocioEdu: Sociological Education, 2026)
The phenomenon of educational dualism in the Buntet Pesantren environment is reflected in santri who simultaneously pursue formal education at Madrasah Aliyah Negeri (MAN) 3 Cirebon, which implements the Merdeka Curriculum, and traditional education at Pesantren Riyyadussholihin grounded in salaf traditions. This study examines the dynamics of learning processes and actor actions in navigating these two educational systems through Talcott Parsons’ structural-functionalism, using the AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). The research used a qualitative case study approach, data were collected through participatory observation, documentation, and in-depth interviews with students, teachers, and pesantren authorities.The findings reveal that Adaptation is achieved through flexible scheduling and curriculum synchronization between institutions. Goal Attainment reflects a dual orientation toward academic achievement and professional careers in the madrasah, alongside the pursuit of barakah (spiritual blessing) in the pesantren. Integration is primarily mediated by the kyai, who bridges traditional values and modern educational demands, while Latency is maintained through symbolic systems that enable role-switching. This study concludes that systemic equilibrium is sustained by pesantren cultural values that effectively integrate critical rationality within a cohesive educational framework.